2020
DOI: 10.1186/s12935-020-01248-1
|View full text |Cite
|
Sign up to set email alerts
|

HE4 overexpression decreases pancreatic cancer Capan-1 cell sensitivity to paclitaxel via cell cycle regulation

Abstract: Background: Paclitaxel is a first-line chemotherapy drug for pancreatic, ovarian, endometrial cancers and other malignancies. However, its efficacy is often compromised by decreased cell sensitivity or the development of resistance. Human epididymis protein 4 (HE4) is highly expressed in gynecologic and pancreatic cancer tissues, and its serum levels are used for patient triage and assistant diagnosis of gynecologic cancers. Previous studies have shown that HE4 overexpression could promote cancer cell prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…Li et al (30) reported that HE4 overexpression in endometrial cancer cells promoted cell proliferation, stromal infiltration, and other malignant behaviors of cancer cells. HE4 overexpression promotes the proliferation of CAPAN-1 pancreatic cells and significantly reduces the cells' paclitaxel sensitivity (31). Ribeiro et al (32) indicated that overexpression of HE4 resulted in increased resistance of the SKOV3 and OVCAR8 OC cell lines to cisplatin and paclitaxel, and that HE4 knockout could partially reverse resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al (30) reported that HE4 overexpression in endometrial cancer cells promoted cell proliferation, stromal infiltration, and other malignant behaviors of cancer cells. HE4 overexpression promotes the proliferation of CAPAN-1 pancreatic cells and significantly reduces the cells' paclitaxel sensitivity (31). Ribeiro et al (32) indicated that overexpression of HE4 resulted in increased resistance of the SKOV3 and OVCAR8 OC cell lines to cisplatin and paclitaxel, and that HE4 knockout could partially reverse resistance.…”
Section: Discussionmentioning
confidence: 99%
“…( 30 ) reported that HE4 overexpression in endometrial cancer cells promoted cell proliferation, stromal infiltration, and other malignant behaviors of cancer cells. HE4 overexpression promotes the proliferation of CAPAN-1 pancreatic cells and significantly reduces the cells’ paclitaxel sensitivity ( 31 ). Ribeiro et al.…”
Section: Discussionmentioning
confidence: 99%
“…Another gene that seems to have a specific role in the chemoresistance of PDAC is human epididymis protein 4 that causes both cancer cell growth and reduced sensitivity to paclitaxel in PDAC cell lines. These results suggest that HE4 expression levels may be used to predict the sensitivity of PDAC patients to paclitaxel [ 39 ].…”
Section: Mechanisms Underlying Resistance To the Gemcitabine Plus Nab...mentioning
confidence: 99%
“…For example, the lncRNA PITPNA-AS1/miR-876-5p/c-MET axis regulates the cell cycle, and promotes the progression of cervical cancer [23]. Additionally, HE4 overexpression reduces the sensitivity of pancreatic cancer to paclitaxel by deregulating the cell cycle pathway [24]. Glycyrrhizic acid represses the proliferation of gastric cancer cells by inhibiting the cell cycle [25].…”
Section: Validation Of Hub Related Genesmentioning
confidence: 99%